PENGARUH PEMBERIAN KUNYIT DAN TEMULAWAK MELALUI AIR MINUM TERHADAP RESPON FISIOLOGIS BROILER - Bomy .; Syahrio Tantalo; Siswanto . (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2014)
This study aimed to determine the effect of the use of turmeric and ginger in the drink water onphysiological responses broiler and determine the best treatment of the physiological responsesbroiler. The experiment was conducted in February – March 2013 in the experimental cagesowned by PT. Rama Jaya Lampung is located in the village of Fajar Baru II, Jati Agung District,South Lampung Regency. Chickens used were as many as 180 Cobb broiler strain tail. Thisresearch was conducted using Completely Randomized Design with three treatments and sixreplications. The treatment given in this research is T0 : normal drink water; T1 : turmeric boiledwater 10 g/600 ml, and T2 : ginger boiled water 10 g/600 ml. Physiological responses samplingperformed 10 % of the number of experimental units. Then the data were analyzed using a rangeof 5% significance level and atau1% (Steel and Torrie, 1993). Variables measured wererespiratory rate, heart rate, and rectal temperature. Based on the results of this study thatadministration of turmeric and ginger on broiler aged 16 and 24 days did not significantly affectrespiratory rate, heart rate, and rectal temperature.